2014
DOI: 10.1016/j.cell.2014.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Coreceptor Scanning by the T Cell Receptor Provides a Mechanism for T Cell Tolerance

Abstract: Summary In the thymus, high affinity, self-reactive thymocytes are eliminated from the pool of developing T cells, generating central tolerance. Here, we investigate how developing T cells measure self-antigen affinity. We show that very few CD4 or CD8 coreceptor molecules are coupled with the signal-initiating kinase, Lck. To initiate signaling, an antigen engaged T cell receptor (TCR) scans multiple coreceptor molecules to find one that is coupled to Lck. Coreceptor scanning is the first and rate-limiting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
255
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(274 citation statements)
references
References 66 publications
11
255
3
Order By: Relevance
“…Immunoprecipitation of whole-cell lysates (WCLs) from CD4WT cells revealed that ∼6% of the CD4 signal was associated with Lck relative to the CD4-Lck fusion after detection with a flow-based flourophore-linked immunosorbant assay (FFLISA) (Fig. 1A), similarly to what has been shown for DP thymocytes (17). Interestingly, immunoprecipitation from CD4T WCL indicated that ∼3% of the CD4 signal was associated with Lck relative to the fusion even though CD4T lacks the clasp that mediates association with Lck.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Immunoprecipitation of whole-cell lysates (WCLs) from CD4WT cells revealed that ∼6% of the CD4 signal was associated with Lck relative to the CD4-Lck fusion after detection with a flow-based flourophore-linked immunosorbant assay (FFLISA) (Fig. 1A), similarly to what has been shown for DP thymocytes (17). Interestingly, immunoprecipitation from CD4T WCL indicated that ∼3% of the CD4 signal was associated with Lck relative to the fusion even though CD4T lacks the clasp that mediates association with Lck.…”
Section: Resultssupporting
confidence: 57%
“…Thus, a higher frequency of CD4-associated Lck would be available for recruitment to TCR-pMHC interactions. One prediction of these results is that the CD4-Lck cells should be more sensitive to lower affinity TCR-pMHC interactions if activation depends on the frequency of Lck-associated CD4 molecules encountered during the course of TCR-pMHC interactions (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these ligands have equivalent binding to H-2A b but differ in their ability to stimulate B3K508 TCR transgenic T cells (24,26). The thymic selection potential of 3K and its variants was recently assessed using fetal thymic organ culture (27). The ligands 3K, P5R, and P2A induced strong negative selection of developing B3K508 thymocytes, while the ligand P-1A elicited only partial thymocyte deletion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental removal of Lck by genetic manipulation is a useful tool to probe signals downstream of the TCR and will mimic the status of aging lymphocytes that lose expression of Lck (21,22). In Lck-sufficient T cells, Lck activation upon TCR binding can be influenced also by the extent and duration of coreceptor recruitment, which happens when T cells are stimulated by altered peptide ligands with low affinities (23)(24)(25). A consequence of stimulation by altered peptide ligands is that the expansion potential of T cells is curtailed compared with that induced by strong agonist ligands (3).…”
Section: Weak Alternate Peptide Ligands Stimulate Ribosome Biogenesismentioning
confidence: 99%